Performance of Tetranychus urticae (Acari: Tetranychidae) on three hop cultivars (Humulus lupulus) - Savi, Patrice Jacob [UNESP]; Gonsaga, Renan Furlan [UNESP]; de Matos, Sidnéia Terezinha Soares [UNESP]; Braz, Leila Trevisan [UNESP]; de Moraes, Gilberto José; de Andrade, Daniel Júnior [UNESP] (Springer Nature, 2021)
Tetranychus urticae Koch (Acari: Tetranychidae) is a major pest species in numerous crops including hop (Humulus lupulus L.). Substantial T. urticae infestation was observed to occur in this recently introduced crop in Brazil. The adoption of less suitable cultivars to the pest species is highly desirable for integrated pest management. We used free-choice trials and two-sex life table analysis to determine the preference and population growth of T. urticae under laboratory conditions using three of hop cultivars currently expanding in Brazil (Mantiqueira, Victoria, and Yakima Gold). We also estimated the density of non-glandular trichomes and lupulin glands found on the abaxial leaf surface of these cultivars and correlated them with performance parameters of T. urticae. Mantiqueira appeared to be the least preferred by adult females for attractiveness and oviposition suggesting existence of antixenosis on this cultivar. Female immature stages developed slower on Yakima Gold and Mantiqueira, but no difference was observed between the latter and Victoria. Fecundity and longevity were significantly lower on Mantiqueira than on Victoria and Yakima Gold. No significant differences were observed among cultivars for intrinsic rate of increase (r), finite rate of increase (λ), and net rate of reproduction (R0), suggesting the absence of antibiosis. Although, lupilin gland densities were higher on Mantiqueira and Yakima Gold than on Victoria, no significant correlations were observed between these defensive traits and performance parameters of T. urticae. However, 30-day population simulations of T. urticae suggest that Yakima Gold is the least susceptible, Mantiqueira is moderately susceptible, and Victoria is highly susceptible.
Keywords: Age-stage and two-sex life table; Demographic parameters; Free-choice test; Hop plant; Two-spotted spider mite